POTENSI WIRAUSAHA DIVERSIFIKASI PRODUK Zingiberaceae BERBASIS KEARIFAN LOKAL DI KECAMATAN SAJOANGING, KABUPATEN WAJO, SULAWESI SELATAN - Syamsuri Syamsuri; Hasria Alang (BUANA SAINS, 2021)
This research aimed to see the entrepreneurial potential of diversification of Zingiberaceae products based on local wisdom in Sajoanging Subdistrict, Wajo Regency, South Sulawesi. Location determination has been done by the purposive sampling method. The focus of the study was the utilization of Zingiberaceae based on local wisdom. The subject of the study was the local food product processing society. Data collection techniques are done through interviews. Data analysis methods are used qualitatively. The results showed that Zingiberaceae is found in Sajoanging Subdistrict and has entrepreneurial potential namely fesse, onnyi, onnyi pute, likku, temmu, Cekku, fanini and lippujang. The entrepreneurial potential of diversification of Zingiberaceae products based on local wisdom in Sajoanging Subdistrict, Wajo Regency is utilized as a traditional medicinal ingredient, among others used as headache, cough, itchy medicine, stomach pain medicine, internal medicine, and heat reduction. As a traditional cosmetic, namely as a material for making bedda tettu, bedda, lotong and pappisau. As a traditional culinary, it is used in the manufacture of nasu likku, nasu palekko and sarabba. It means that Zingiberaceae can process into various products that have added value and encourage economic growth in the village.